Electrocardiogram-synchronized pulsatile extracorporeal life support preserves left ventricular function and coronary flow in a porcine model of cardiogenic shock - Ostadal, Petr; Mlcek, Mikulas; Gorhan, Holger; Simundic, Ivo; Strunina, Svitlana; Hrachovina, Matej; Krüger, Andreas; Vondrakova, Dagmar; Janotka, Marek; Hala, Pavel; Mates, Martin; Ostadal, Martin; et al. (PloS one, 2018)
INTRODUCTION: Veno-arterial extracorporeal life support (ECLS) is increasingly being used to treat rapidly progressing or severe cardiogenic shock. However, it has been repeatedly shown that increased afterload associated with ECLS significantly diminishes left ventricular (LV) performance. The objective of the present study was to compare LV function and coronary flow during standard continuous-flow ECLS support and electrocardiogram (ECG)-synchronized pulsatile ECLS flow in a porcine model of cardiogenic shock. METHODS: Sixteen female swine (mean body weight 45 kg) underwent ECLS implantation under general anesthesia and artificial ventilation. Subsequently, acute cardiogenic shock, with documented signs of tissue hypoperfusion, was induced by initiating global myocardial hypoxia. Hemodynamic cardiac performance variables and coronary flow were then measured at different rates of continuous or pulsatile ECLS flow (ranging from 1 L/min to 4 L/min) using arterial and venous catheters, a pulmonary artery catheter, an LV pressure-volume loop catheter, and a Doppler coronary guide-wire. RESULTS: Myocardial hypoxia resulted in declines in mean cardiac output to 1.7±0.7 L/min, systolic blood pressure to 64±22 mmHg, and LV ejection fraction (LVEF) to 22±7%. Synchronized pulsatile flow was associated with a significant reduction in LV end-systolic volume by 6.2 mL (6.7%), an increase in LV stroke volume by 5.0 mL (17.4%), higher LVEF by 4.5% (18.8% relative), cardiac output by 0.37 L/min (17.1%), and mean arterial pressure by 3.0 mmHg (5.5%) when compared with continuous ECLS flow at all ECLS flow rates (P<0.05). At selected ECLS flow rates, pulsatile flow also reduced LV end-diastolic pressure, end-diastolic volume, and systolic pressure. ECG-synchronized pulsatile flow was also associated with significantly increased (7% to 22%) coronary flow at all ECLS flow rates. CONCLUSION: ECG-synchronized pulsatile ECLS flow preserved LV function and coronary flow compared with standard continuous-flow ECLS in a porcine model of cardiogenic shock.
Keywords: Disease Models, Animal; modely nemocí na zvířatech; koronární cirkulace; Extracorporeal Membrane Oxygenation; funkce levé komory srdeční; hemodynamika; prasata; Shock, Cardiogenic; Ventricular Function, Left; Animals; Life Support Care; Coronary Circulation; Coronary Vessels; mimotělní membránová oxygenace; Electrocardiography; Pulsatile Flow; zvířata; Hemodynamics; Swine; ženské pohlaví; koronární cévy; Female; resuscitační péče; kardiogenní šok; elektrokardiografie; pulzatilní průtok